2011
DOI: 10.3354/meps09313
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in trophic interactions of green sea turtles Chelonia mydas on a relatively pristine coastal foraging ground

Abstract: Adult green sea turtles Chelonia mydas are often the largest-bodied herbivores in their communities and may play an important role in structuring seagrass and macroalgal communities. Recent studies, however, suggest that green turtles might be more omnivorous than previously thought. We used animal-borne video and nitrogen and carbon stable isotopic analysis of skin to elucidate diets of green turtles in the relatively pristine seagrass ecosystem of Shark Bay, Australia. Stable isotope values suggested that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 79 publications
3
89
1
1
Order By: Relevance
“…However, inference from the stable isotope ratios of green turtle eggs suggested that some nesting females in the Ogasawara Islands consumed a substantial proportion of invertebrates prior to breeding migration (Hatase et al 2006). Consumption of animal matter by green turtles in other parts of the world has been confirmed by direct observation of episodic ingestion or inferred from stable isotope data or both (Heithaus et al 2002, Seminoff et al 2006b, Amorocho & Reina 2007, Arthur et al 2007, Cardona et al 2010, Burkholder et al 2011, Lemons et al 2011). …”
Section: N · Chelonia Mydasmentioning
confidence: 96%
“…However, inference from the stable isotope ratios of green turtle eggs suggested that some nesting females in the Ogasawara Islands consumed a substantial proportion of invertebrates prior to breeding migration (Hatase et al 2006). Consumption of animal matter by green turtles in other parts of the world has been confirmed by direct observation of episodic ingestion or inferred from stable isotope data or both (Heithaus et al 2002, Seminoff et al 2006b, Amorocho & Reina 2007, Arthur et al 2007, Cardona et al 2010, Burkholder et al 2011, Lemons et al 2011). …”
Section: N · Chelonia Mydasmentioning
confidence: 96%
“…Turtles fed predominantly on items on the sea floor, often using the foreflippers to clear debris and locate prey items. Unlike sympatric green turtles that frequently fed on scyphozoan jellyfish or ctenophores in the water column (Burkholder et al 2011), mid-water foraging was observed only twice for loggerhead turtles. In these cases, feeding occurred out of the field of view and was inferred from head and neck movements so prey could not be identified.…”
Section: Foraging Behaviormentioning
confidence: 99%
“…Our goal instead was to conduct a preliminary investigation of isotopic niche variation within this population and provide a foundation for more detailed behavioral and isotopic research. Isotope signatures of basal resources in our study area have been analyzed in a study of the foraging ecology of sympatric green turtles (Burkholder et al 2011). …”
Section: Stable Isotope Analysismentioning
confidence: 99%
“…However, green turtle diet can vary by foraging ground (Bjorndal 1985(Bjorndal , 1997, life stage (Bolten 2003), and the availability of food sources (Garnett et al 1985). Recent studies using stable isotope analysis and animalborne videos suggested more variation in green turtle diet than previously thought (Vander Zanden et al 2010, Burkholder et al 2011.…”
Section: Introductionmentioning
confidence: 97%